Ameliorative Effects of Acacia Honey against Sodium Arsenite-Induced Oxidative Stress in Some Viscera of Male Wistar Albino Rats. (3rd December 2013) - Aliyu, Muhammad; Ibrahim, Sani; Inuwa, Hajiya M.; Sallau, Abdullahi B.; Abbas, Olagunju; Aimola, Idowu A.; Habila, Nathan; Uche, Ndidi S.
Abstract : Cancer is a leading cause of death worldwide and its development is frequently associated with oxidative stress-induced by carcinogens such as arsenicals. Most foods are basically health-promoting or disease-preventing and a typical example of such type is honey. This study was undertaken to investigate the ameliorative effects of Acacia honey on sodium arsenite-induced oxidative stress in the heart, lung and kidney tissues of male Wistar rats. Male Wistar albino rats divided into four groups of five rats each were administered distilled water, Acacia honey (20%), sodium arsenite (5 mg/kg body weight), Acacia honey, and sodium arsenite daily for one week. They were sacrificed anesthetically using 60 mg/kg sodium pentothal. The tissues were used for the assessment of glutathione peroxidase, catalase, and superoxide dismutase activities, protein content and lipid peroxidation. Sodium arsenite significantly( P < 0.05 ) suppressed the glutathione peroxidase, catalase, superoxide dismutase activities with simultaneous induction of lipid peroxidation. Administration of Acacia honey significantly increased( P < 0.05 ) glutathione peroxidase, catalase, and superoxide dismutase activities with concomitant suppression of lipid peroxidation as evident by the decrease in malondialdehyde level. From the results obtained, Acacia honey mitigates sodium arsenite induced-oxidative stress in male Wistar albino rats, which suggest that it may attenuate oxidative stress implicated in chemical carcinogenesis.